Regulatory loop between lncRNA FAS-AS1 and DNMT3b controls FAS expression in hydroquinone-treated TK6 cells and benzene-exposed workers. (June 2020) - Yuan, Qian; Zhang, Haiqiao; Pan, Zhijie; Ling, Xiaoxuan; Wu, Minhua; Gui, Zhiming; Chen, Jialong; Peng, Jianming; Liu, Zhidong; Tan, Qiang; Huang, Dongsheng; Xiu, Liangchang; et al.
Abstract: Hydroquinone (HQ), one of the main metabolites of benzene, is a well-known human leukemogen. However, the specific mechanism of how benzene or HQ contributes to the development of leukemia is unknown. In a previous study, we demonstrated the upregulation of DNA methyltransferase (DNMT) expression in HQ-induced malignant transformed TK6 (HQ-TK6) cells. Here, we investigated whether a regulatory loop between the long noncoding RNA FAS-AS1 and DNMT3b exists in HQ-TK6 cells and benzene-exposed workers. We found that the expression of FAS-AS1 was downregulated in HQ-TK6 cells and workers exposed to benzene longer than 1.5 years via histone acetylation, and FAS-AS1 expression was negatively correlated with the time of benzene exposure. Restoration of FAS-AS1 in HQ-TK6 cells promoted apoptosis and inhibited tumorigenicity in female nude mice. Interestingly, treatment with a DNMT inhibitor (5-aza-2-deoxycytidine), histone deacetylase inhibitor (trichostatin A), or DNMT3b knockout led to increased FAS-AS1 through increased H3K27ac protein expression in HQ-TK6 cells, and DNMT3b knockout decreased H3K27ac and DNMT3b enrichment to the FAS-AS1 promoter region, which suggested that DNMT3b and/or histone acetylation involve FAS-AS1 expression. Importantly, restoration of FAS-AS1 resulted in reduced expression of DNMT3b and SIRT1 and increased expression of FAS in both HQ-TK6 cells and xenograft tissues. Moreover, the average DNMT3b expression in 17 paired workers exposed to benzene within 1.5 years was decreased, but that of the remaining 103 paired workers with longer exposure times was increased. Conversely, DNMT3b was negatively correlated with FAS-AS1 expression. Both FAS-AS1 and DNMT3b influenced the enrichment of H3K27ac in the FAS promoter region by regulating the expression of SIRT1, consequently upregulating FAS expression. Taken together, these observations demonstrate crosstalk between FAS-AS1 and DNMT3b via a mutual inhibition loop and indicate a new mechanism by which FAS-AS1 regulates the expression of FAS in benzene-related carcinogenesis. Graphical abstract: Image 1 Highlights: LncRNA FAS-AS1 and DNMT3b were dynamically expressed in hydroquinone (HQ)-treated TK6 cells and peripheral blood samples of benzene-exposed workers. LncRNA FAS-AS1 and DNMT3b formed a mutual inhibition loop. The regulatory loop constituting lncRNA FAS-AS1 and DNMT3b downregulated the expression of FAS through histone acetylation in HQ-induced malignant transformed TK6 cells.